THE QUALITY OF TUBERCULOSIS SERVICES IN PATIENTS’ PERSPECTIVES: A LITERATURE REVIEW - Aufiena Nur Ayu Merzistya; Mateus Sakundarno Adi; Dwi Sutiningsih; Sri Ratna Rahayu (Universitas Airlangga, 2021)
Background: The assessment from the patient's perspective is the assurance of TB service’ quality to achieve the